COVID-19 vaccine uptake among physicians during the second wave of COVID-19 pandemic: Attitude, intentions, and determinants: A cross-sectional study - Amer, Samar A.; Shah, Jaffer; Abd-Ellatif, Eman Elsayed; El Maghawry, Hala A. (Frontiers in Public Health, 2022)
Background Developed within a short period of time, the COVID-19 vaccine is not yet widely accepted among the public despite its availability, including by physicians, who are considered a vulnerable group. Methodology A descriptive cross-sectional study selected 436 governmental physicians from different specializations, representing four random administrative regions in Egypt. The data were collected through a self-administrated online questionnaire and analyzed using suitable tests. Results Out of the studied 436 physicians, 229 (52.2%) [aged 20–30, 284 (65.1%)] were women, 270 (61.9%) were residents, 219 (50.2%) were married, 398 (91.3%) were non-smokers, and 263 (60.3%) were non-frontline caregivers. The majority of the physicians, 227 (52.1%) of them, hesitated to take the vaccine, 236 (54.1%) had not decided on the preferred type of vaccine, and 101 (23.2%) were neutrally confident in the Egyptian healthcare system; 302 (96.3%) had no history of drug or food hypersensitivity. There was no statistically significant (p < 0.05) relationship between the physicians' attitude toward COVID-19 vaccine uptake and the studied demographic variables. There was a statistically significant connection between all of the doctors' intentions to get the COVID-19 vaccine and all of the four attitude domains that were looked at. Conclusion The study concluded that a low level of willingness among Egyptian physicians to take the COVID-19 vaccine is a prevalent problem. COVID-19 vaccination hesitancy and non-acceptance were linked to negative attitudes about natural immunity, mistrust of vaccine benefits, and concerns about commercial profiteering.